2020
DOI: 10.1002/jdd.12495
|View full text |Cite
|
Sign up to set email alerts
|

“I don't think the problem's the student…I think it's us”: Engaging faculty in curriculum innovation

Abstract: Purpose The need to innovate predoctoral dental education is well established; however, there are few recent reports to guide substantial curriculum transformation. The purpose of this study was to describe faculty perspectives on their vision of future graduates, curriculum needs, and potential barriers to a successful redesign. This information would be used to inform strategic planning for the predoctoral curriculum transformation. Methods Eighty full‐time faculty from the University of North Carolina Adams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…In this research, we identified opportunities to better support faculty during curriculum change through the creation of the ASC. This needs assessment demonstrated faculty encounter numerous pain points such as time, resources, knowledge, confidence, organizational structure, and culture; these findings were consistent with previous research about challenges in curriculum change process 18 . Moreover, faculty identified three opportunities to address these pain points including the support of teaching and learning practices, enhancing the faculty experience, and assisting with education evaluation and scholarship.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…In this research, we identified opportunities to better support faculty during curriculum change through the creation of the ASC. This needs assessment demonstrated faculty encounter numerous pain points such as time, resources, knowledge, confidence, organizational structure, and culture; these findings were consistent with previous research about challenges in curriculum change process 18 . Moreover, faculty identified three opportunities to address these pain points including the support of teaching and learning practices, enhancing the faculty experience, and assisting with education evaluation and scholarship.…”
Section: Discussionsupporting
confidence: 85%
“…A challenge during significant moments of change—such as substantial curriculum revisions—is promoting faculty engagement and ensuring their perspective remains visible 14,15,18 . In this research, we identified opportunities to better support faculty during curriculum change through the creation of the ASC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations